Teacher’s Directive Speech Acts to Special Needs Students in EFL Class Interaction at Junior High School - Zuhrotun Nisa Saragih; Maslatif Dwi Purnomo; Sholihatul Hamidah Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the types and strategies of teachers’ directive speech acts and the responses of special needs students during English learning and classroom interaction at the junior high school level. Using a qualitative approach, the data were obtained naturally from classroom communication to capture authentic linguistic behaviour. The findings reveal four types of directive speech acts used by teachers, namely commands, prohibitions, suggestions, and imperatives, each serving distinct instructional and behavioural purposes. The analysis also shows that teachers employ both direct and indirect strategies in delivering directives, which are adapted to students’ cognitive, emotional, and linguistic conditions. Furthermore, the responses of special needs students vary according to the nature of the directive, the clarity of the instruction, and the contextual demands of the classroom situation. Some students respond promptly and appropriately, while others require repetition, modelling, or simplified instructions to process and perform the requested actions. Overall, the realization of the directive types, strategies, and student responses is shaped by the diverse interactional contexts in special needs classrooms, demonstrating that effective teacher directives must be flexible and sensitive to students’ individual characteristics. These findings highlight the importance of pragmatic awareness in instructional communication, particularly in supporting the engagement and participation of students with special needs in EFL learning.